2013
DOI: 10.1186/1742-2094-10-100
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin induces inflammation after preterm intraventricular hemorrhage by methemoglobin formation

Abstract: BackgroundCerebral intraventricular hemorrhage (IVH) is a major cause of severe neurodevelopmental impairment in preterm infants. To date, no therapy is available that prevents infants from developing serious neurological disability following IVH. Thus, to develop treatment strategies for IVH, it is essential to characterize the initial sequence of molecular events that leads to brain damage. In this study, we investigated extracellular hemoglobin (Hb) as a causal initiator of inflammation in preterm IVH.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 37 publications
7
89
0
3
Order By: Relevance
“…High levels of methemoglobin have been reported in CSF after IVH. 22,23 We will continue to pursue the potential role of Fe 2 þ in IVH-induced brain injury in other studies, but this is hampered by a lack of specific chelators available for ferrous iron.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of methemoglobin have been reported in CSF after IVH. 22,23 We will continue to pursue the potential role of Fe 2 þ in IVH-induced brain injury in other studies, but this is hampered by a lack of specific chelators available for ferrous iron.…”
Section: Discussionmentioning
confidence: 99%
“…Once Hb escapes the intra-RBC compartment, it is highly reactive and activates cytotoxic, oxidative and inflammatory pathways, eventually leading to tissue damage [8,9]. Extracellular Hb is rapidly oxidised from ferrous (Fe 2+ , denoted oxyHb) to ferric (Fe 3+ , denoted metHb) Hb [10,11], which readily releases the heme group [12]. Heme is highly lipophilic and binds to lipids intercalating into cell membranes, which results in toxic cytolytic effects [13].…”
Section: A Highly Reactive and Potentially Cytotoxic Proteinmentioning
confidence: 99%
“…In a preterm rabbit pup model of IVH, it was recently shown that extracellular Hb infiltrates and is widely dispersed in large regions of the cerebral periventricular white matter, especially in areas with high extracellular plasticity [37]. Furthermore, metHb was shown to be a potent inducer of pro-inflammation, displaying a strong correlation with TNF protein levels in intraventricular CSF and increased mRNA levels for TNF, IL-1β and of HO-1 in periventricular brain tissue [10,38].…”
Section: Aetiology and Studies Of Hb-related Brain Damage In Animal Mmentioning
confidence: 99%
“…When the cells reached approximately 90% confluence CSF from preterm infants with IVH, metHb and hemin (prepared immediately prior to the experiment, as described above) were added to the HCPEpiC cultures, and the cells were incubated for 4-24 h as indicated in the figure legends. The metHb and hemin concentrations used were in accordance with previously described concentrations in CSF from preterm infants with IVH [22]. After incubation, the cells were harvested using either QiazolQ Lysis reagent (for RNA extraction; QIAGEN, Germantown, Md., USA) or cell extraction buffer (for protein extraction; Invitrogen, Camarillo, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the hemorrhage is confined to the intraventricular space and results in a progressive ventricular enlargement very similar to that seen in preterm human infants [21]. In a recent study using this model and primary astrocyte cell cultures we showed that IVH is followed by a release of cell-free hemoglobin (Hb) in the intraventricular space and that accumulated Hb metabolites are causal inducers of inflammation [22]. In addition to the in vivo characterization of AQP1, 4 and 5, here we further investigated the effects of Hb metabolites on the expression of AQP1, 4 and 5 in primary human choroid plexus epithelial cells (HCPEpiC) and compared the response to that following exposure to posthemorrhagic CSF obtained from preterm human infants.…”
Section: Introductionmentioning
confidence: 99%